Strategi Pengaruh Human Resource Information System Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Divisi HRD & GA PT. Sumi Rubber Indonesia - Inez Gracia Hapsari; Rini Fatmawati; Setya Prihatiningtyas (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Thei purpose ofi this studyi was toi analyze thei influence of Humani Resource Informationi System oni employee performancei through jobi satisfactioni as an interveningi variable ini the HRD & GA division of iPT. Sumi Rubber Indonesia. iThis aims ofi this studyi include: 1) To knowi the influencei of Humani Resource iInformation Systemi on employeei performance; 2) To knowi the influencei of Humani Resource Informationi System on jobi satisfaction; 3) To knowingi the influencei of jobi satisfaction on employeei performance; and 4) To knowi the influencei of Humani Resource Informationi System on employeei performancei through jobi satisfaction. Thisi study wasi conductedi by explanatoryi quantitative methodi with researchi samplei ofi 60 respondents. Thei samplingi techniquei was carriedi out using simplei randomi sampling technique, andi datai analysisi usingi pathi analysis, partiali test, simultaneousi test, iand coefficienti of determinationi test withi the helpi of SPSS (Statisticali Programi for iSocial Science) versioni 25.0 iprogram. Thei resultsi ofi thisi studyi cani bei concluded, ithat: 1) Humani Resourcei Informationi Systemi has noi significanti effecti oni employee performance; 2) Humani Resourcei Informationi Systemi has a positivei and isignificant effecti oni jobi satisfaction; 3) Jobi satisfaction has a positivei and isignificant effecti on employeei performance; and 4) Humani Resourcei Informationi Systemi effects employee performancei through jobi satisfaction.